Repression of autophagy leads to acrosome biogenesis disruption caused by a sub-chronic oral administration of polystyrene nanoparticles. (May 2022) - Zhou, Lixiao; Yu, Ziying; Xia, Yinyin; Cheng, Shuqun; Gao, Jieying; Sun, Wei; Jiang, Xuejun; Zhang, Jun; Mao, Lejiao; Qin, Xia; Zou, Zhen; Qiu, Jingfu; et al.
Graphical abstract: Highlights: Sperm quality of mice were declined after oral administration to PS-NPs. PS-NPs altered the ultrastructure of acrosome and disrupted acrosome biogenesis. PS-NPs-induced acrosome biogenesis disruption was linked with autophagy repression. Abstract: As a new widespread contaminant, nanoplastics (NPs) pose a potential risk to human health. Nevertheless, the adverse effects of NPs on the male reproductive system are poorly understood. In this study, we aimed to determine the effects of polystyrene nanoplastics (PS-NPs) (50 nm) on sperm quality, with a focus on the acrosome defects. After 35 days of intragastric administration, sperm quality was decreased and testicular structures were impaired in mice exposed to PS-NPs in both the medium (1.0 mg/kg) and high dose (10 mg/kg) groups. No significant changes were observed in the low dose (0.2 mg/kg) group. Meanwhile, acrosome parameters including acrosome integrity and acrosome reaction were decreased after the administration of PS-NPs. These findings were consistent with the disruption of acrosome biogenesis, as identified by the changed testicular ultrastructure. Additionally, the findings were further validated using seven marker genes ( Gba2, Pick1, Gopc, Hrb, Zpbp1, Spaca1 and Dpy19l2 ) essential for acrosome formation, which showed that two of these genes ( Gopc and Dpy19l2 ) were significantly down-regulated. Moreover, repressed autophagy was observed in the testes of PS-NPs-exposed mice based on autophagy-related protein expression. This phenomenon was further verified in GC-2spd cells treated with PS-NPs (50 μg/mL, 100 μg/mL, 200 μg/mL for 24 h). The potential role of autophagy in such acrosome defects was explored by using the autophagy inhibitor 3-methyladenine (3-MA), autophagy activator rapamycin or beclin-1 siRNA. The results showed that Golgi-associated vesicle disorganization was exacerbated with the 3-MA and beclin-1 siRNA pretreatments, but decreased with the rapamycin pretreatment, and the expression of GOPC and DPY19L2 was also altered. These results indicated that autophagy might be involved in the PS-NPs-induced acrosome lesions based on the regulation of two key acrosome-formation proteins, GOPC and DPY19L2. Altogether, our results will provide new insights into the PS-NPs-induced male reproductive impairment.